Case Report: Two cases of bronchiolar adenoma/ciliated muconodular papillary tumor characterized by significant basal cell hyperplasia and squamous metaplasia - Gao, Ziran; Feng, Qiang; Wang, Yuanyuan; Jiang, Ya; Han, Dan; Xu, Wenmang (Frontiers in Oncology, 2025)
BackgroundBronchiolar adenoma/ciliated muconodular papillary tumor (BA/CMPT) is a rare benign pulmonary tumor from the bronchiolar epithelium. Histologically, it features a continuous basal cell layer and luminal cells. Its resemblance to invasive mucinous adenocarcinoma (IMA) and acinar adenocarcinoma complicates intraoperative frozen section diagnosis. When accompanied by extensive basal cell hyperplasia (BCH) and squamous metaplasia, it may mimic sclerosing pneumocytoma or adenosquamous carcinoma. This study presents two rare BA/CMPT cases with extensive BCH and squamous metaplasia.Case presentationCase 1: A 62-year-old female was found to have a mixed ground-glass nodule in the right lower lung lobe on CT, raising suspicion of malignancy. She received a thoracoscopic segmentectomy. Histology revealed alveolar epithelial proliferation with extensive BCH and focal squamous metaplasia. Diagnosis: distal-type BA with BCH and squamous metaplasia.Case 2: A 67-year-old female had a solid nodule in the right lower lobe detected by CT, and a thoracoscopic wedge resection was performed. Histopathological examination revealed a lesion composed of ciliated and mucinous luminal cells overlying extensive BCH and areas of squamous metaplasia, with focal atypia observed in the basal cell layer. Diagnosis: proximal-type BA with BCH and atypical squamous metaplasia. IHC demonstrated that luminal cells in both cases expressed TTF-1, while basal cells expressed CK5/6, P63, and P40. Next-generation sequencing (NGS) did not identify any mutations or fusions in common driver oncogenes such as EGFR, BRAF, or KRAS. Postoperative follow-up showed no evidence of tumor recurrence or metastasis in either case.ConclusionBA with extensive BCH and squamous metaplasia is rare and presents diagnostic challenges due to overlap with conditions such as sclerosing pneumocytoma, adenosquamous papilloma, adenosquamous carcinoma, mucoepidermoid carcinoma, and epithelial-myoepithelial carcinoma. Accurate diagnosis during intraoperative frozen section analysis is crucial for guiding appropriate surgical decision-making. IHC is essential for confirming the diagnosis.